Evaluation of the peritoneal surface disease severity score (PSDSS) in ovarian cancer patients undergoing cytoreductive surgery and HIPEC: Two pathogenetic types based study. Issue 8 (14th May 2018) - Yarema, Roman; Fetsych, Taras; Volodko, Natalya; Оhorchak, Myron; Petronchak, Orest; Huley, Roman; Mylyan, Yuriy; Glehen, Olivier
Abstract : Background and Objectives: Clinical experience suggests that cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) play an important role in the management of ovarian cancer. In order to improve patient selection, the peritoneal surface disease severity score (PSDSS) was previously introduced for use in colorectal cancer patients. However, almost no data exist regarding the utility of the PSDSS index in ovarian cancer patients. Methods: A retrospective study of the effectiveness of CRS and HIPEC was carried out in 59 patients with ovarian cancer. The PSDSS was based on three criteria: symptoms, extent of peritoneal dissemination, and primary tumor structure as assessed by histology and biomarker expression. Results: The overall survival time for patients with ovarian cancer in PSDSS Stage I was 48 ± 25.3 months. For PSDSS Stage II, the survival time was 26.5 ± 4.7 months. For PSDSS Stage III, it was 15.5 ± 4 months, and for PSDSS Stage IV, it was 6 ± 4.3 months. A multivariate analysis showed that the PSDSS stage was the only independent survival predictor. Conclusions: These data demonstrate that a PSDSS based on two pathogenetic types may be useful for predicting survival outcomes in ovarian cancer patients treated with CRS/HIPEC.